Oedipus and the Devil : witchcraft, sexuality, and religion in early modern Europe - Roper, Lyndal (London ; New York : Routledge, 1994)
This bold and imaginative book marks out a different route towards understanding the body, and its relationship to culture and subjectivity. Amongst other subjects, Lyndal Roper deals with the nature of masculinity and feminity.
Book Cover; Title; Contents; List of plates; Preface; Acknowledgements; Introduction; Was there a crisis in gender relations in sixteenth-century Germany?; Will and honour: sex, words and power in Augsburg criminal trials; Sexual utopianism in the German Reformation; Blood and codpieces: masculinity in the early modern German town; Stealing manhood: capitalism and magic in early modern Germany; Drinking, whoring and gorging: brutish indiscipline and the formation of Protestant identity; Exorcism and the theology of the body; Witchcraft and fantasy in early modern Germany.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Sex role -- Europe -- History; Witchcraft -- Europe -- History; Popular culture -- Europe -- History; Witchcraft -- Europe -- History; Witchcraft -- history; Gender Identity -- history; Rôle selon le sexe -- Europe -- Histoire; Sorcellerie -- Europe -- Histoire; Culture populaire -- Europe -- Histoire; SOCIAL SCIENCE -- Gender Studies; Popular culture; Sex role; Witchcraft; Europe; Sexo e sexualidade (sociologia); Historia moderna; Cultura; Religiao; Sexualität; Religion; Hexerei; Deutschland; Hekserij; Sekseverschillen; Femmes -- Europe de l'Ouest -- Conditions sociales -- 16e siècle.; Rôle selon le sexe -- Europe -- Histoire; Sorcellerie -- Europe -- Histoire; Culture populaire -- Europe -- Histoire; Sorcellerie et sexualité -- Europe -- Histoire; Sexualité -- Aspect religieux -- Christianisme; Augsbourg (Allemagne) -- Moeurs et coutumes -- 16e siècle.; Allemagne -- Moeurs et coutumes -- 16e siècle.; Sex roles -- History; Witchcraft -- History; Europe; History